Establish the extended regulon of the RamA regulator by performing ChIPseq - Saxena, Aishwarya (The University of Edinburgh, 2020)
[No Deposit Agreement]
To establish the extended regulon of the RamA regulator by performing ChIPseq
Keywords: RamA regulator; ChIPseq; transcriptional regulator; antimicrobial resistance; Klebsiella pneumoniae; DNA binding sites